Aphrodite Philommêdês in the Theogony. (23rd October 2015) - Bouchard, Elsa
Abstract: Discussion of Aphrodite's epithet philommeidês/philommêdês in Hesiod Theogony 200. Hesiod's aetiological account of this name suggests the meaning 'wiles-loving' as well as 'genitals-loving'. This interpretation is supported by a number of episodes from Archaic poetry in which literary or mythical figures make use of a ruse to permit the fulfilment of their erotic longing, or conversely exploit someone else's desire as a means to achieve supremacy in a power struggle.